2018
DOI: 10.1002/sctm.17-0219
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells for Severe Intraventricular Hemorrhage in Preterm Infants: Phase I Dose-Escalation Clinical Trial

Abstract: We previously demonstrated that transplanting mesenchymal stem cells (MSCs) improved recovery from brain injury induced by severe intraventricular hemorrhage (IVH) in newborn rats. To assess the safety and feasibility of MSCs in preterm infants with severe IVH, we performed a phase I dose‐escalation clinical trial. The first three patients received a low dose of MSCs (5 × 106 cells/kg), and the next six received a high dose (1 × 107 cells/kg). We assessed adverse outcomes, including mortality and the progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 46 publications
1
92
0
3
Order By: Relevance
“…Although 74% of the publications reported some promising results, only 18% of the publications showed that this treatment was safe [115]. Although the safety of MSC transplantation was confirmed, less than 40% of the studies and clinical trials with available and published results showed [128] positive improvements in the use of MSCs for patients with amyotrophic lateral sclerosis [116]. Administration of MSCs in clinical trials exhibited beneficial effects on diabetes.…”
Section: Clinical Application Of Mscsmentioning
confidence: 99%
“…Although 74% of the publications reported some promising results, only 18% of the publications showed that this treatment was safe [115]. Although the safety of MSC transplantation was confirmed, less than 40% of the studies and clinical trials with available and published results showed [128] positive improvements in the use of MSCs for patients with amyotrophic lateral sclerosis [116]. Administration of MSCs in clinical trials exhibited beneficial effects on diabetes.…”
Section: Clinical Application Of Mscsmentioning
confidence: 99%
“…The study was performed by intraventricular injection of allogeneic UCB‐MSCs in nine preterm infants with severe IVH, with a follow‐up to 40 weeks of corrected age (Table ). The outcomes indicated that UCB‐MSC therapy was well tolerated with attenuated periventricular hemorrhagic infarct, and no infants suffered from dose‐limiting toxicities or serious adverse reactions such as anaphylaxis or death within 6 hr after injection (Ahn et al, ). Although the results were encouraging, randomized controlled clinical trials with long‐term follow‐up are necessary.…”
Section: Ucb‐sc Therapy In Preterm Brain Injuries and Neurological Sementioning
confidence: 99%
“…For example, autologous cord blood was imported back into preterm infants to test for any therapeutic effects on various complications (Sun et al, ), and autologous UCBC therapy has been applied in preterm infants with WMI (Cotten et al, ; Li et al, ) . Also, allogeneic UCB‐derived mesenchymal stem cells (UCB‐MSCs) have been administered in preterm infants with severe IVH (Ahn, Chang, Sung, & Park, ). These studies suggest that the application of autologous and allogeneic UCB‐SCs in preterm infants is feasible and safe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanically, MSCs function in vivo via direct differentiation or paracrine action. The therapeutic potential of MSC engraftment has been proved in premature infant diseases, and early clinical trials in preterm neonates with BPD (NCT01297205 [9], NCT01632475 [10]) and severe intraventricular hemorrhage (NCT02274428 [11]) have been conducted. A myriad of bioactive factors are readily available in the conditioned medium (CM) of MSCs and the medium can mediate multiple known functions of MSCs, such as angiogenesis, anti-brosis and anti-in ammatory effects [12].…”
Section: Introductionmentioning
confidence: 99%